Genetic Divergence, Implication of Diversity, and Conservation of Silkworm, Bombyx mori. (13th May 2014) - Bindroo, Bharat Bhusan; Manthira Moorthy, Shunmugam
Abstract : Genetic diversity is critical to success in any crop breeding and it provides information about the quantum of genetic divergence and serves a platform for specific breeding objectives. It is one of the three forms of biodiversity recognized by the World Conservation Union (IUCN) as deserving conservation. Silkworm Bombyx mori, an economically important insect, reported to be domesticated over 5000 years ago by human to meet his requirements. Genetic diversity is a particular concern because greater genetic uniformity in silkworm can increase vulnerability to pests and diseases. Hence, maintenance of genetic diversity is a fundamental component in long-term management strategies for genetic improvement of silkworm which is cultivated by millions of people around the worlds for its lusture silk. In this paper genetic diversity studies carried out in silkworm using divergent methods (quantitative traits and biochemical and molecular markers) and present level of diversity and factors responsible for loss of diversity are discussed.